External Conflict Faced By The Main Characters In Elemental: Forces Of Nature Movie - Yanti, Ni Putu Jelita Krishna; Skolastika, I Made Perdana (Denpasar Institute, 2024)
This study aims to identify the external conflicts faced by the main characters in the movie Elemental: Forces of Nature. External conflict is a struggle between a character and an outside force. This force can be another character, society, nature, or a physical obstacle. It's when a character faces challenges that come from their environment or other people, rather than from their own mind or emotions. The objective is to categorize the different types of external conflicts encountered by the characters. Data analysis was conducted using Kenney’s (1966) theory. The data obtained were collected through observation and note-taking, which involved watching the movie and marking parts that expressed the conflict. The data was analyzed using qualitative method and presented descriptively. This study uncovers various external conflicts that the characters face in Elemental: Forces of Nature movie. These conflicts predominantly occur between Ember and Wide, the main characters and their surrounding environment. The findings illustrate how the main characters' interactions with external forces shape their journey and development within the storyline. By categorizing these conflicts, the study provides a deeper understanding of the character dynamics within the movie